Alvin Stockton gets Phillipp J. Leyendecker award (Raton Range Raton, New Mexico, 1977)
Article on Alvin Stockton receiving the first to receive the New Mexico State University's Phillip J. Leyendecker Agriculturist of Distinction award.
Master list item #:38
File location is in the Raton File Cabinet
Keywords: Stockton, Alvin; Leyendecker, Phillip J; New Mexico State University; Denver University; New Mexico Cattle Growers Association; New Mexico Farm and Livestock Bureau; Springer Boy's school; New Mexico Colfax County Hospital; Local History; Biography; Award; Agriculture; Livestock; Raton, New Mexico